Neuroscience data integration through mediation: An (F)BIRN case study - Ashish, Naveen; Ambite, José Luis; Muslea, Maria; Turner, Jessica A. (Frontiers in Neuroinformatics, 2010)
We describe an application of the BIRN mediator to the integration of neuroscience experimental data sources. The BIRN mediator is a general purpose solution to the problem of providing integrated, semantically-consistent access to biomedical data from multiple, distributed, heterogeneous data sources. The system follows the mediation approach, where the data remains at the sources, providers maintain control of the data, and the integration system retrieves data from the sources in real-time in response to client queries. Our aim with this paper is to illustrate how domain-specific data integration applications can be developed quickly and in a principled way by using our general mediation technology. We describe in detail the integration of two leading, but radically different, experimental neuroscience sources, namely, the Human Imaging Database (HID), a relational database, and the eXtensible Neuroimaging Archive Toolkit (XNAT), an XML web services system. We discuss the steps, sources of complexity, effort and time required to build such applications, as well as outline directions of ongoing and future research on biomedical data integration.